Exploring University Students’ Perceptions of Watching Movies for English Listening Development - Brilian Bagaskara; Puspa Dewi; Andrian Nuriza Johan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Abstract   This study aims to examine university students’ perceptions of watching English-language movies for listening development, focusing on perceived impact, attitudes, and learning obstacles. Although audiovisual media are widely used in English language learning, limited research has examined learners’ subjective experiences in listening development, especially within the Indonesian EFL context. A descriptive qualitative design was employed involving five undergraduate students from an English Education department at Muhammadiyah University of Purworejo. Participants were selected through purposive sampling based on their experience in using English-language movies as an educational tool. Data were collected through structured questionnaires and semi-structured interviews and analyzed using descriptive frequency analysis and thematic analysis. The findings show that students perceive English movies as beneficial for improving listening comprehension, increasing exposure to authentic spoken language, and enhancing familiarity with native speakers’ accents and speech patterns. Students also demonstrate positive attitudes, reflected in increased motivation, enjoyment, and reduced anxiety during listening activities. However, they encounter several obstacles, including fast speech rate, background sounds, and limited vocabulary, which hinder comprehension. The study concludes that English movies serve as an effective supplementary medium for listening development, although pedagogical support such as subtitles, vocabulary preparation, and repeated viewing is required to optimize learning outcomes.